Insertion/deletion-related polymorphisms in the human T cell receptor beta gene complex (The Rockefeller University Press, 1989)
Insertion/deletion related polymorphisms (IDRP) involving stretches of 15-30 kb within the human TCR-beta gene complex were revealed by pulse- field gel electrophoresis. Two independent IDRP systems were detected by analysis of Sfi I- and Sal I-digested human DNA samples using probes for TCR C and V region gene segments. The allelic nature of these systems was verified in family studies, and mapping data allowed localization of one area of insertion/deletion among the V gene segments and the other near the C region genes. All but one of 50 individuals tested could be typed for the two allelic systems, and gene frequencies for the two allelic forms were 0.37/0.61 and 0.46/0.54, indicating that these polymorphisms are widespread.